The Ability of the 4th Semester Students of English Education Study Program of Muhammadiyah University Palu in Writing Paragraph: Kemampuan Mahasiswa Semester 4 Program Studi Pendidikan Bahasa Inggris Universitas Muhammadiyah Palu in Writing Paragraf - Fenia Ninut; Asri Hente; Sari (Jurnal Kolaboratif Sains, 2021)
The purpose of this research is to find out the ability of the 4th semester students of English department in writing descriptive paragraph. The subject of the research is the 4th semester students in academic year of 2017 consisting of seven students. This research used qualitative descriptive method.Written test and interview as techniques of data collection, and technique of data analysis were used percentage that was described qualitatively. Research finding shows that the mean score of the seven students is 77. Three of the seven students got 81, 82, 89.They belonged to excellent and good categories, and four students got 71, 72,74 and 66, they belonged to enough and poor categories. The result of interview indicated the seven students have different difficulties or problems; most the students faced problems on content and language uses.